Running injuries and the associated factors in marathon runners - Chang, W. L.; Chen, W.-Y.; Shih, Y.-F. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
This study disclosed that various risk factors were linked to injuries in the lower extremity. The practitioner could use these information in preventing running associated injury and pain.